Immediate effects of Ukrainian phytocomposition on biophotonics (GDV), EEG and HRV parameters - Oksana Fihura; Sofiya Ruzhylo; Xawery Żukow; Igor Popovych (Kazimierz Wielki University, 2021)
Background. Back in 2015, we registered short-term reactions to the Ukrainian phytocomposition of electroencephalogram and heart rate variability parameters. At the same time, we also recorded the reactions of biophotonics (GDV) parameters, but due to the skepticism of Ukrainian academic science regarding this method, we did not dare to include the results in the article. Materials and methods. The object of observation were 12 women (44±13 years) and 62 men (44±12 years) with dysfunction of neuro-endocrine-immune complex. GDV, HRV and EEG parameters were recorded in the morning in basal conditions. Then the members of the main group used 5 ml of phytocomposition dissolved in 45 ml of tap water, instead in the control group used 50 ml of the latter. After 1,5 hours, the test was repeated. Results. Discriminant analysis revealed 26 EEG, 6 HRV and 7 GDV parameters characteristic of the initial state and after consumption of phytocomposition or tap water. The use of balm causes the normalizing decrease of increased sympathotonic markers and the increase of decreased vagotonic markers. Physiologically favorable vegetotropic effects of the balm are accompanied by a further increase in the initially increased activity of β-rhythm-generating cortical and subcortical structures as well as activation of θ-rhythm-generating and inhibition of α- and δ-rhythm-generating nuclei whose initial activity was within normal limits. Neurotropic effects are accompanied by a decrease in fractality and entropy and an increase in the area of GDI, as well as the energy of the first, fourth, fifth and seventh chakras (virtual). Conclusion. Ukrainian phytocomposition "Balm Truskavets'" causes favorable immediate neurotropic and biophysic changes at patients with dysfunction of neuro-endocrine-immune complex.